The Effect of Tumor Angiogenesis Agents on Tumor Growth Dynamics: A Mathematical Model - Ali Mohseni; Mohammad Pooyan; Somayeh Raiesdana; Mohammad Bagher Menhaj (Frontiers in Biomedical Technologies)
Purpose: Tumor-induced angiogenesis is a dangerous state of the tumor growth process in which solid tumors have a blood supply. Modeling has been a very important tool in studying tumor growth and angiogenesis. In this paper, we developed a cancer model by introducing tumor angiogenesis agents to better highlight the role of these chemical substances in tumor-induced vascularization. Our model can reconstruct the transition from a pre-angiogenic to a post-angiogenic state.